Implementation of Consumer Legal Protection in Electronic Transactions - Iqbal Yuzha Pratama; Rhiznanda Fazrin Maulana; Fajri Panggabean; Harmono; Dadan Taufik Fathurohman (Indonesian Journal of Business Analytics, 2025)
The development of online transactions through social media presents convenience and risks for consumers, mainly due to the lack of regulations and legal protection mechanisms.  The goal of this study is to look at how Law Number 8 of 1999 on Consumer Protection is applied to online transactions and see how much legal protection consumers get. The method utilized is normative legal and follows the law. The problem being studied is how customers are protected by law when they buy things online through social media The study's results show that although normative protection has been regulated, its implementation is still weak due to low law enforcement, a lack of information, and often irresponsible business actors. This study recommends strengthening regulations, consumer education, and stricter law enforcement.